Human Resource Management in the BRICS countries: a comparative study - Lima, Luciana Campos; Zuppani, Tatiani dos Santos; Maclennan, Maria Laura Ferranty (Interações, 2017)
The objective of the study is to investigate the contextual characteristics of BRICS countries on Human Resource Management (HRM) policies and practices. For that we used secondary data analysis, such as reports, journals, and newspapers. Data is organized in order to provide logical support for the arguments presented. The main findings relate institutional environment characteristics from the education system and labour market with: (i) recruitment and selection practices; (ii) remuneration systems; (iii) training and development practices.